The Foley grail : the art of performing sound for film, games, and animation - Ament, Vanessa Theme (New York : Focal Press, 2014)
Foley artist Vanessa Theme Ament teaches you how Foley is designed, crafted, and edited for any project, right down to the nuts and bolts of spotting, cueing, and performing sounds. Various renowned sound artists provide a treasure trove of shortcuts, hot tips, and other tricks of the trade. Provides the tools you need to produce vibrant, realistic soundcapes that will lift your media projects to the next level.
Includes bibliographical references and index.
Keywords: Motion pictures -- Sound effects; Animated films -- Sound effects; Video games -- Sound effects; Animation (Cinematography); Digital video; Video digital